2022
DOI: 10.1042/bcj20210522
|View full text |Cite
|
Sign up to set email alerts
|

Immunothrombosis and the molecular control of tissue factor by pyroptosis: prospects for new anticoagulants

Abstract: The interplay between innate immunity and coagulation after infection or injury, termed immunothrombosis, is the primary cause of disseminated intravascular coagulation (DIC), a condition that occurs in sepsis. Thrombosis associated with DIC is the leading cause of death worldwide. Interest in immunothrombosis has grown because of COVID-19, the respiratory disease caused by SARS-CoV-2, which has been termed a syndrome of dysregulated immunothrombosis. As the relatively new field of immunothrombosis expands at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 177 publications
0
15
0
Order By: Relevance
“…Numerous studies depicted in Table 4 suggest that pathogens induce monocyte-derived TF expression and release in the circulation, which in turn activates the extrinsic coagulation pathway. The binding of LPS to transmembrane receptors such as TLR4 in monocytes induces TF mRNA expression via NF-κB activation ( 166 ). Moreover, the interaction of pathogen components either with TLRs or directly with intracellular pathways in monocytes can result in inflammasome activation and subsequent TF release via pyroptosis ( 163 , 166 ).…”
Section: Monocytes In Immunothrombosismentioning
confidence: 99%
“…Numerous studies depicted in Table 4 suggest that pathogens induce monocyte-derived TF expression and release in the circulation, which in turn activates the extrinsic coagulation pathway. The binding of LPS to transmembrane receptors such as TLR4 in monocytes induces TF mRNA expression via NF-κB activation ( 166 ). Moreover, the interaction of pathogen components either with TLRs or directly with intracellular pathways in monocytes can result in inflammasome activation and subsequent TF release via pyroptosis ( 163 , 166 ).…”
Section: Monocytes In Immunothrombosismentioning
confidence: 99%
“…In conclusion, clinical and experimental evidence establish cellular death mediated by inflammasomes as a key trigger for immunothrombosis and microvascular thrombosis [ 22 ]. Two key signals are required for the coagulation activation mediated by the inflammasome: induction of TF protein and inflammatory caspase activation that induce TF release through pyroptosis [ 23 ] ( Figure 1 ).…”
Section: Inflammasome Activationmentioning
confidence: 99%
“…Several studies have shown that hemostasis can be spared with effective thromboprotection, among them it has been demonstrated that a modified heparin without anticoagulant activity blocks HMGB1, inhibiting the caspase-11 mediated pyroptosis, preventing sepsis, thrombosis, and mortality in mice, without increasing hemorrhagic risk [ 65 ]. It is possible that coagulopathy may be better prevented by inflammasome inhibition of the TF induction rather than by the coagulation factor inhibition [ 17 , 23 ].…”
Section: Immunothrombosis As a New Therapeutical Targetmentioning
confidence: 99%
“…TF is a 47-kDa membrane glycoprotein and receptor and the key trigger of infection-and injury-induced coagulation [5,[22][23][24]. TF is critical for survival, as deletion in mice leads to universal embryonic death [25][26][27], and defects in TF gene expression are associated with differing clinical outcomes in patients with severe sepsis [28].…”
Section: Tissue Factor: the Initiator Of Trauma-induced Coagulationmentioning
confidence: 99%